Safeness, subjective and objective changes after turbinate surgery in pediatric patients: A systematic review. (August 2020) - Calvo-Henriquez, Christian; Capasso, Robson; Martínez-Capoccioni, Gabriel; Rangel-Chaves, Jesús; Liu, Stanley Yung; O'Connor-Reina, Carlos; Lechien, Jerome R.; Martin-Martin, Carlos
Abstract: Objective: Inferior turbinates are the main structure related to impaired nasal breathing. When medical treatment fails, surgery is the next step, according to clinical guidelines. However, despite the widespread acceptance of this procedure, there is some controversy about performing it in children. Data sources: Pubmed (Medline), the Cochrane Library, EMBASE, Scopus, Science direct, SciELO and Trip Database. Review methods: We looked for articles in which the individual outcome of turbinate surgery in pediatric patients was investigated independently of whether it was the main objective of the study or not. Results: 13 papers (1111 patients) met the inclusion criteria. 6 authors performed diverse objective assessment and 11 authors used subjective scales. All of them found improvement after surgery. Due to the heterogeneity of the methods used, they could not be included in a metanalysis. Eleven out of the 13 authors reported 3.12% complication rates, being minor bleeding the most common (1.30%), followed by crust (0.49%) and pain (0.47%). Conclusions: There is a lack of high quality studies in children. Turbinate surgery in children is a safe technique with low complication rates. The available evidence suggests improvement in subjective outcomes after turbinate surgery in children. We cannot make a formal recommendation of a surgical technique in children given the lack of high quality studies, and since comparison between available papers is not possible. Although the evidence at our disposal is weak, it suggests that the safest techniques are MAIT, radiofrequency, coblation and laser.